2007
DOI: 10.1200/jco.2006.09.8822
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Overexpression and Phosphorylation of Epidermal Growth Factor Receptor (EGFR) and the Presence of Truncated EGFRvIII in Locoregionally Advanced Breast Cancer

Abstract: EGFR expression, but not phospho-EGFR or EGFRvIII expression, is an independent adverse prognostic factor in patients with high-risk primary breast cancer, particularly when it is coexpressed with HER-2. Our results suggest the potential benefit of dual EGFR/HER-2 receptor targeting in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
61
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 61 publications
3
61
0
Order By: Relevance
“…(16) Whether Rab5A played any role in these is not clear; there are few data available on the expression of Rab5A in human breast cancer or its impact on disease progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(16) Whether Rab5A played any role in these is not clear; there are few data available on the expression of Rab5A in human breast cancer or its impact on disease progression.…”
mentioning
confidence: 99%
“…(15) Poor prognosis was confirmed in patients of locally advanced breast cancer with overexpression of EGFR. (16) Whether Rab5A played any role in these is not clear; there are few data available on the expression of Rab5A in human breast cancer or its impact on disease progression.…”
mentioning
confidence: 99%
“…Regardless, some patients also experience intrinsic and acquired resistance, eventually leading to disease progression (2). Several mechanisms of trastuzumab resistance have been elucidated, such as intrinsic alteration in HER2-like truncated HER2 receptors (34), heterodimer formation between other receptor tyrosine kinases (RTKs) and HER2 (35)(36)(37), and constitutive activation of the phosphoinositide 3-kinase (PI3K)/AKT pathway or loss of phosphatase and tensin homolog function (38). Studies have suggested that dual HER2 blockade with trastuzumab and pertuzumab may be significantly associated with clinical outcomes (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of EGFR is one of clinical features of breast cancer correlating with poor prognosis (36)(37)(38)(39)(40). Many types of molecular targeting drugs against EGFR have been developed for various cancer types including breast cancer (41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%